Penguatan Kesadaran Masyarakat melalui Penyuluhan Kebersihan Lingkungan Di Kelurahan Sepang - Ananda, Zahra Fika; Istianah, Istianah; Akbar, Riski; Mundzir, Ahmad Bachtiar; Itang, Itang (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The waste problem in Sepang Village, Taktakan District, Serang City is a serious challenge due to the community’s low awareness of cleanliness and limited waste management facilities. This community service program aims to enhance knowledge, foster collective awareness, and encourage community participation in environmental care. The program applied the Participatory Action Research (PAR) approach, emphasizing active community involvement. The activities included outreach by the Environmental Agency, interactive discussions, communal clean-up, ecobrick-making practice, and the installation of educational boards on waste decomposition. The results showed improved community understanding of waste impacts, revived collective cooperation, and appreciation of ecobrick as a practical solution. Challenges such as uneven participation and limited facilities remain important notes for follow-up. Overall, the program highlights that environmental change requires a collective process, consistency, and continuous support.